The parenthood penalty in mental health: Evidence from Austria and Denmark - Alexander Ahammer; Ulrich Glogowsky; Martin Halla; Timo Hener (Johannes Kepler University of Linz, Department of Economics, 2023)
Using Austrian and Danish administrative data, we examine the impacts of parenthood on mental health equality. Parenthood imposes a greater mental health burden on mothers than on fathers. It creates a long-run gender gap in antidepressant prescriptions of about 93.2% (Austria) and 64.8% (Denmark). Further evidence suggests that these parenthood penalties in mental health are unlikely to reflect differential help-seeking behavior across the sexes or the biological effects of giving birth to a child. Instead, they seem to mirror the psychological effects of having, raising, and investing in children. Supporting this interpretation, matched adoptive mothers (who do not experience the biological impacts of childbirth) also encounter substantial parenthood penalties. Moreover, mothers who invest more in childcare (by taking extended maternity leave in quasi-experimental settings) are more likely to face mental health problems.
Keywords: D63; J13; I10; J16; J22; 330; Gender equality; fertility; parenthood; motherhood; mental health; parental leave